GELIAT E-COMMERCE DAN PENERIMAAN PAJAK DIMASA PANDEMI - Tenriwaru Tenriwaru; Amiruddin Amiruddin; Ilma Sahrani (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
This study aims to determine tax revenue from the e-commerce sector during this pandemic. Sources of data used in this study consisted of primary data and secondary data. Primary data were obtained from informants who were taxpayers and tax authorities while secondary data were obtained from relevant written media, namely journals and internet sites. The analysis method used is descriptive qualitative. The results showed that the use of e-commerce during this pandemic was very high compared to previous years, but tax revenue itself actually decreased during this pandemic due to the economic downturn that hit various business sectors which had an impact on decreasing tax revenue.